2018
DOI: 10.1021/acsinfecdis.7b00111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Mycothiol-Dependent Nitroreductase from Mycobacterium tuberculosis

Abstract: The success of Mycobacterium tuberculosis (Mtb) as a pathogen depends on the redundant and complex mechanisms it has evolved for resisting nitrosative and oxidative stresses inflicted by host immunity. Improving our understanding of these defense pathways can reveal vulnerable points in Mtb pathogenesis. In this study, we combined genetic, structural, computational, biochemical, and biophysical approaches to identify a novel enzyme class represented by Rv2466c. We show that Rv2466c is a mycothiol-dependent nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…Importantly, NFC-resistant mutants were selected which had mutations in the gene encoding Rv2466c. This indicates that the MSH-dependent nitroreductase activity of Rv2466c is crucial for pro-drug activation [28] . Rv2466c has a DsbA-like structure and can also function as mycoredoxin-2 in demycothiolation with electrons from the MSH/Mtr pathway [30] .…”
Section: Biosynthesis and Functions Of Mycothiol And Bacillithiol In mentioning
confidence: 94%
See 2 more Smart Citations
“…Importantly, NFC-resistant mutants were selected which had mutations in the gene encoding Rv2466c. This indicates that the MSH-dependent nitroreductase activity of Rv2466c is crucial for pro-drug activation [28] . Rv2466c has a DsbA-like structure and can also function as mycoredoxin-2 in demycothiolation with electrons from the MSH/Mtr pathway [30] .…”
Section: Biosynthesis and Functions Of Mycothiol And Bacillithiol In mentioning
confidence: 94%
“…MSH further contributes to antibiotic resistance in Mycobacterium tuberculosis ( Mtb ). MSH is required for activation of the pro-drugs isoniazid (INH) and nitrofuranylcalanolides (NFCs) which are potent anti-mycobacterial drugs [27] , [28] . INH is activated by the catalase KatG and MSH, leading to NAD-INH adduct formation and inhibition of the enoyl -ACP reductase (InhA) of the mycolic acid biosynthesis pathway [29] .…”
Section: Biosynthesis and Functions Of Mycothiol And Bacillithiol In mentioning
confidence: 99%
See 1 more Smart Citation
“…A novel MSH-dependent reductase (Rv2466c) involved in the activation of the pro-drug TP052, a thieno-pyrimidine derivative able to kill Mtb , was found to be essential for bacterial survival during exposure to H 2 O 2 (Newton et al, 2011; Albesa-Jové et al, 2014; Rosado et al, 2017). Recently, it was shown that Rv2466c functions as a noncanonical nitroreductase that relies on MSH for the reduction of nitro-containing compounds (Negri et al, 2018). Under oxidative stress conditions, Mtb increases (via sigma H, E, and B) the expression of thioredoxin reductase/thioredoxin together with enzymes involved in MSH synthesis (Raman et al, 2001; Newton and Fahey, 2008).…”
Section: Pathogen Virulence and Antioxidant Networkmentioning
confidence: 99%
“…For example, we have recently demonstrated that the intracellular pathogen R. equi carries genes encoding three mycoredoxins with overlapping roles during host cell infection, being necessary at least one of them for intracellular survival [70]. This is important, because their partially overlapping roles may explain why other authors had not observed any attenuation in mutant strains carrying deletions on just one of the mycoredoxins present in the genome of other actinobacterial pathogens, such as M. tuberculosis [75]. Overall, the structure of the Brx and Mrx redoxins is well conserved among different bacterial species [67,70,76], which may explain their overlapping roles in maintaining the redox homeostasis of different intracellular pathogens.…”
Section: Enzymatic Reparation Mechanisms Of Protein Oxidationmentioning
confidence: 99%